PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KARYAWAN UD. SANTOSO KEDIRI - Dinda Indriana; Rike Kusuma Wardhani; Diana Ambarwati (CV SWA Anugrah, 2024)
This research aims to determine the influence of work motivation and Work Discipline on UD Employee Productivity. Santoso Kediri. As for The variables of this research are Work Motivation (X1), Work Discipline (X2) and Employee Productivity (Y). This research uses quantitative methods using data collection techniques in the form of interviews, observations, studies literature and questionnaires. Meanwhile, the analysis used is a validity test, test reliability, coefficient of determination test, multiple linear regression test, t test and F test. Sampling in this research used purposive sampling with the consideration of all UD employees. Santoso Kediri, numbering 32 person.The results of this research used the SPSS 22.0 program The significant level is 5% or 0.05 with result (1) partially working motivation has a significant effect on employee productivity with a significant value 0.021 < 0.05 which means Ha1 is accepted and Ho1 is rejected. (2) partially Discipline Work has a significant effect on employee productivity and value significant 0.000 < 0.05 which means Ha2 is accepted and Ho2 is rejected. (3) according to Simultaneous Work Motivation and Work Discipline have a significant effect on Employee Productivity with a significant value of 0.000 < 0.05 which means Ha3 accepted and Ho3 rejected